PREGNANT WOMENS PERCEPTION ON HIGH-RISK PREGNANCY - Rosmawati, Rosmawati; Wijaksanah, Eka; Sarliana, Sarliana (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Central Java province is one of the contributors to maternal mortality rate (MMR) in Indonesia which reached 126 per 100.000 live births. The cause of death of pregnant women can be predicted based on the risk factors posed by the mother during pregnancy. In 2014 the number of high-risk pregnant women in Semarang City is 2.904 people and this number increased in 2015. Aims: To explore the perception of pregnant women about high risk pregnancy at Bandarharjo Health Center Semarang City. Methods: This is a qualitative research study with phenomenology approach. The sampling technique used is purposive sampling and the sample criteria in this study were the third-trimester pregnant women and did not have a high-risk pregnancy, living in work area of health center of Bandarharjo Semarang City, doing a pregnancy check up at Bandarharjo Semarang health center, and willing to become an informant. The sample in this study amounted to 7 participants, consisting of 4 informants and 3 triangulation. Triangulation in this research is a midwife at Health Center Bandarharjo Semarang City and another pregnant women who does not become an informant and live in working area of Bandarharjo Health Center Semarang City. Data collection techniques for both informants and triangulation used in-depth interviews. Results: All the informant understand that high-risk pregnancies is a condition in which maternal pregnancies at high risk for both mother and baby. The information about high-risk pregnancy obtained from health workers, the public, reading books, and media. Midwives play as an important source when pregnant women looking for the information about high risk pregnancy. Most of informants revealed they never wished to be in high-risk pregnancies, but they know about the impact of high risk pregnancy. The informants also agreed if they have to go health facilities if they get a high risk pregnancy. Conclusion: Overall pregnant women already understand about high-risk pregnancies. Midwives play an important role in the welfare of mothers and babies so that the information provided is very beneficial for pregnant women. Therefore, it is expected that cooperation from various parties refers to the government, health workers, community and individual pregnant women themselves in conducting activities such as counseling that can provide benefits, especially in the prevention of pregnancy with high risk.Â